A Phenomenological Study of Pre-service Teachers’ Readiness in Integrating Digital Literacy for Mathematics Assessment - Umi Hanifah; Masriyah; Ayu Silvi Lisvian Sari; Nurus Saadah; Jessica Dwi Nur Cahyani (Universitas Negeri Surabaya, 2026)
Digital literacy has become an essential competence for mathematics educators, particularly in the domain of assessment. This study aims to explore the lived experiences and readiness of pre-service mathematics teachers in integrating digital literacy into mathematics assessment practices. The research employed a transcendental phenomenological approach to capture the essence of participants’ experiences in designing and implementing digital-based assessments. The participants consisted of six final-year pre-service mathematics teachers from two Indonesian universities who had experience developing digital assessment tasks during their teaching practice. Data were collected through semi-structured interviews, classroom observations, and analysis of digital assessment artifacts, including GeoGebra-based activities and Quizizz assessments. The data were analyzed using a phenomenological reduction process involving epoché, horizonalization, clustering of meaning units, and synthesis of the essence of the phenomenon. The findings reveal that although pre-service teachers demonstrate strong operational skills in using digital tools, their readiness to design meaningful digital mathematics assessments varies. Three main themes emerged from the analysis: technological fluency, pedagogical considerations in digital assessment design, and alignment between digital tools and assessment rubrics. The results indicate that readiness to integrate digital literacy in mathematics assessment involves not only technical competence but also the integration of pedagogical reasoning and assessment literacy. These findings highlight the importance of integrating digital assessment training within teacher education programs to better prepare future mathematics teachers for technology-supported assessment practices.